2017
DOI: 10.1016/j.semarthrit.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effects of immunosuppressive medications and risk factors for post-operative joint infection following total joint arthroplasty in patients with rheumatoid arthritis or osteoarthritis

Abstract: Objective Inconclusive findings about infection risks, importantly the use of immunosuppressive medications, in patients who have undergone large-joint total joint arthroplasty challenge efforts to provide evidenced-based perioperative total joint arthroplasty recommendations to improve surgical outcomes. Thus, the aim of this study was to describe risk factors for developing a postoperative infection in patients undergoing TJA of a large joint [total hip arthroplasty, total knee arthroplasty, or total shoulde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 32 publications
5
34
0
Order By: Relevance
“…While the increased risk of infection has been attributed to therapy with immunosuppressant medications including DMARDs and biologics, an association with post-operative infection has never been demonstrated directly in randomized controlled trials performed at the time of surgery. The relationship of post-operative infection to anti-rheumatic medication use is unproven, although [32][33][34] a meta-analysis has demonstrated an increased risk of infection associated with TNFi exposure around the time of surgery when data was pooled [35], a conclusion supported by additional observational studies [15,[34][35][36]. However, a recent study that used billing data to specify the timing of infliximab infusions in relation to surgery found no clear increase in risk of infection when infliximab was infused within 4 weeks of surgery compared to longer periods of drug withholding [34].…”
Section: Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the increased risk of infection has been attributed to therapy with immunosuppressant medications including DMARDs and biologics, an association with post-operative infection has never been demonstrated directly in randomized controlled trials performed at the time of surgery. The relationship of post-operative infection to anti-rheumatic medication use is unproven, although [32][33][34] a meta-analysis has demonstrated an increased risk of infection associated with TNFi exposure around the time of surgery when data was pooled [35], a conclusion supported by additional observational studies [15,[34][35][36]. However, a recent study that used billing data to specify the timing of infliximab infusions in relation to surgery found no clear increase in risk of infection when infliximab was infused within 4 weeks of surgery compared to longer periods of drug withholding [34].…”
Section: Infectionmentioning
confidence: 99%
“…The increased utilization of potent disease modifying anti-rheumatic drugs (DMARDs) and biologics like the tumor necrosis factor inhibitors (TNFi) has had a clear impact on quality of life for patients with RA, SPA, and SLE, medication use has not been shown to decrease the incidence of large joint arthroplasty for RA, and most RA, PSA, and SLE patients are receiving these immunosuppressant medications at the time of surgery [6][7][8]. While improvements in pain and function outcomes measured pre and post-operatively are excellent after THA and TKA for patients with RA, SPA, and SLE, adverse events, in particular infection, are increased [9][10][11][12][13][14][15][16][17]. Ninety day readmission, most commonly for infection, is also increased for patients with RA [18].…”
Section: Introductionmentioning
confidence: 99%
“…The possible reason is that the BMI of children with CHD in our study is smaller than general population, and the patients with BMI >95th percentile have not reached the [38,39]. However, children with high BMI have a low risk of developing these diseases.…”
Section: Discussionmentioning
confidence: 74%
“…It also suggested that the better nutrition condition may be helpful to prevent nosocomial infection after cardiac surgery in children. In addition, among the adult population, people with high BMI are prone to diabetes, high blood pressure and other diseases, which are risk factors for postoperative infection [37,38].…”
Section: Discussionmentioning
confidence: 99%